In my time of dying: a history of death and the dead in West Africa - Parker, John (Princeton University Press, 2021)
Frontmatter -- Contents -- Illustrations -- Maps -- Acknowledgements -- Introduction -- 1 Cultural Encounter -- 2 Body, Soul and Person -- 3 Speaking of Death -- 4 Grief and Mourning -- 5 Gold, Wealth and Burial -- 6 Faces of the Dead -- 7 The Severed Head -- 8 Slaves -- 9 Human Sacrifice -- 10 Poison -- 11 Christian Encounters -- 12 From House Burial to Cemeteries -- 13 Ghosts and Vile Bodies -- 14 Writing and Reading about Death -- 15 The Colony of Medicine -- 16 Wills and Dying Wishes -- 17 Northern Frontiers -- 18 Reordering the Royal Dead -- 19 Making Modern Deathways -- Conclusion -- Glossary -- Notes -- Index